2014
DOI: 10.1088/0953-8984/26/35/355003
|View full text |Cite
|
Sign up to set email alerts
|

Condensation and evaporation transitions in deep capillary grooves

Abstract: We study the order of capillary condensation and evaporation transitions of a simple fluid adsorbed in a deep capillary groove using a fundamental measure density functional theory (DFT). The walls of the capillary interact with the fluid particles via long-ranged, dispersion, forces while the fluid-fluid interaction is modelled as a truncated Lennard-Jones-like potential. We find that below the wetting temperature Tw condensation is first-order and evaporation is continuous with the metastability of the conde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 35 publications
1
32
0
2
Order By: Relevance
“…These and related studies are also of practical relevance to nanotechnologies involving the fabrication of functional surfaces which control the adsorption of microscopically small amounts of liquid [11]. For geometrically sculpted substrates, theoretical studies of wedges [12][13][14], grooves [15][16][17] and cones [18] have shown that the wall geometry can dramatically alter the adsorption properties and accompanying interfacial fluctuation effects. New transitions also arise for planar but chemically heterogeneous substrates in which the wall is a composite formed by materials with different wetting properties.…”
Section: Introductionmentioning
confidence: 96%
“…These and related studies are also of practical relevance to nanotechnologies involving the fabrication of functional surfaces which control the adsorption of microscopically small amounts of liquid [11]. For geometrically sculpted substrates, theoretical studies of wedges [12][13][14], grooves [15][16][17] and cones [18] have shown that the wall geometry can dramatically alter the adsorption properties and accompanying interfacial fluctuation effects. New transitions also arise for planar but chemically heterogeneous substrates in which the wall is a composite formed by materials with different wetting properties.…”
Section: Introductionmentioning
confidence: 96%
“…In this section we present the DFT results of the condensation in grooves of finite depth D and width L formed of completely wet walls and compare with predictions based on a slab model [24]. The slab model has been used previously [13,18] to analyze the critical behaviour of condensation and evaporation in infinitely deep grooves and it is straightforward to extend the analysis for grooves of finite depths. Within the model one assumes that the one-body fluid density ρ(r) = ρ(x, z) adopts only three values: i) ρ(r) = ρ l , the liquid density at bulk two-phase coexistence, if the fluid occupies the volume near the side and bottom walls as described in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…coexistence between thin and thick liquid films adsorbed on the side walls. These transitions in slit pores are first-order, but in grooves they are continuous, due to the attractive effect of the capping wall, which can nucleate films and capillary liquid metastable in the slit pore [15,16,[18][19][20]38]. Consider approaching the condensation line 1 in Figure 2 at the constant temperature T = 0.87, by thermodynamically quasi-statically advancing from a low value of ∆µ towards the condensation value ∆µ 1 , across the transition lines 6 and 7.…”
Section: Wetting Phenomenologymentioning
confidence: 96%
“…Subsequent studies by Yatsyshin et al [15] and Rascón et al [19] demonstrated the possible existence of a capillary wetting temperature, T cw , which separates firstorder and continuous condensation regimes in the groove. In particular, for systems with dispersive intermolecular fluid-fluid and fluid-substrate interactions, it was shown that above T cw , the height of the meniscus from the capped end diverges on approaching the chemical potential of condensation, µ c , as (µ c − µ) −1/4 [15][16][17][18]20].…”
Section: Introductionmentioning
confidence: 99%